Geografia e Música: "Crucificados pelo sistema" (Ratos de Porão) e sua resistência perante a ditadura empresarial-militar - Santos, Pedro Henrique Campos dos (Universidade Federal de São Carlos, 2025)
This work presents a theoretical-methodological analysis of the album Crucificados Pelo Sistema (1984) by the Brazilian band Ratos de Porão to examine how resistance to the Brazilian dictatorial government of the early 1980s was expressed, utilizing concepts such as musical territory and cultural industry. The study contextualizes the work within the context of Brazilian Punk – a political and social movement that emerged as a reaction to the capitalization of rock, arising from the popular classes to criticize the system and the hegemonic discourse of the Business-Military Dictatorship. The research demonstrates how the album, being the first solo work by a punk band in South America, serves as a historical archive of a youth movement of the time, and also analyzes the Punk movement's efforts to remain underground, resisting co-option by the Cultural Industry through methods like fanzines.
Geography and Music: "Crucified by the system" (Ratos de Porão) and its resistance in the face of the business-military dictatorship
Keywords: Ratos do Porão; Movimento Punk; Ditadura; Indústria cultural; Punk Movement; Dictatorship; Cultural industry; CIENCIAS HUMANAS::GEOGRAFIA::GEOGRAFIA HUMANA; 10. Redução das Desigualdades